2006
DOI: 10.1002/jmri.20624
|View full text |Cite
|
Sign up to set email alerts
|

Proton and sodium MRI assessment of fluid level in calf tissue

Abstract: Purpose:To investigate the feasibility of using 1 H and 23 Na MRI to detect fluid levels in the lower leg muscle. Materials and Methods:Proton and sodium MRI was applied to detect body fluid levels in the lower leg muscles of 18 healthy young male subjects at 3T and 4T. The paradigms under investigation were a postural change from sitting upright to lying supine, and saline infusion. Results:We found that the average proton MR signal in gastrocnemius and soleus muscles were reduced following the postural chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The mean values of TSC measured during this study are in the range of 12 to 21 mmol/L, which corresponds to that usually reported in the literature for healthy skeletal muscle tissue. 24,25 The differences in TSC between muscle groups could be caused by differences in intracellular sodium concentrations or differences in intracellular volume fraction. Due to their variety of functions, leg muscles comprise different fibre types and varying amounts of intramuscular fat and vascularisation.…”
Section: Discussionmentioning
confidence: 99%
“…The mean values of TSC measured during this study are in the range of 12 to 21 mmol/L, which corresponds to that usually reported in the literature for healthy skeletal muscle tissue. 24,25 The differences in TSC between muscle groups could be caused by differences in intracellular sodium concentrations or differences in intracellular volume fraction. Due to their variety of functions, leg muscles comprise different fibre types and varying amounts of intramuscular fat and vascularisation.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous blood volume monitoring measures only relative blood volume changes, which can help reduce hypotensive episodes during dialysis but cannot tell whether a participant has attained their true dry weight or has residual fluid overload (5,6,17). BI is affected by factors like sweat, electrode placement, body shape assumptions, and the validity of population-specific equations, whereas NMR intrinsically measures signal from water molecules (5,17,45). In our head-to-head comparison of BI to magnetic resonance, BI measurements generally performed worse than MRI and comparably to the NMR sensor.…”
Section: Discussionmentioning
confidence: 99%
“…As well a hyperintensity signal due to muscular edema and/or inflammation was visible in two symptomatic patients with FSHD on the TIRM MR image in the soleus lateralis and soleus medialis muscles [14]. It is believed that the muscle MRI study in T2W imaging may find some abnormalities due to increased water in muscle (myoedema) in patients with different myopathies on the early stage and in Pr patients before clinical muscle weakness connected with fatty degeneration [9,13,28,29].…”
Section: Mri Of Lower Limb Muscle Inmentioning
confidence: 96%